2021
DOI: 10.1093/ecco-jcc/jjab076.522
|View full text |Cite
|
Sign up to set email alerts
|

P398 Effect of Intravenous versus Oral Iron Therapy on Physical Fitness and Haemoglobin in Paediatric IBD Patients with Anaemia

Abstract: Background In children and teenagers with Inflammatory Bowel Disease (IBD) and iron deficiency anaemia, administration of iron is recommended to replete empty iron stores, but the most effective route of administration remains unknown. We compared intravenous (IV) and oral iron therapy and evaluated physical fitness and haemoglobin (Hb) improvement over time. Methods We performed an international multicentre randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is yet another legitimate reason mandating the need for robust clinical studies of FCM or any other IV iron complex to showcase an equivalent beneficial outcome in children, including toddlers and pre-schoolers, bearing in mind that FCM has also recently received FDA approval for > 1-year-olds. Recently, a randomised controlled study in 64 children with IBD aged 8–18 years (Prospective Open label study of Parenteral vs Enteral iron in Young IBD patients and Effect on physical fitness [POPEYE study]) was completed and found that FCM was superior to oral iron in terms of early improvement in physical fitness (based on 6-min walking distance) and that the increase in haemoglobin levels was similar for both groups [ 61 ]. There is also an ongoing randomised controlled study enrolling 76 children with IDA aged 1–17 years (ClinicalTrials.gov Identifier: NCT03523117); patients in this study whose response to the control preparation (oral iron) is unsatisfactory will be treated with FCM in a follow-on study (ClinicalTrials.gov Identifier: NCT04269707).…”
Section: Discussionmentioning
confidence: 99%
“…This is yet another legitimate reason mandating the need for robust clinical studies of FCM or any other IV iron complex to showcase an equivalent beneficial outcome in children, including toddlers and pre-schoolers, bearing in mind that FCM has also recently received FDA approval for > 1-year-olds. Recently, a randomised controlled study in 64 children with IBD aged 8–18 years (Prospective Open label study of Parenteral vs Enteral iron in Young IBD patients and Effect on physical fitness [POPEYE study]) was completed and found that FCM was superior to oral iron in terms of early improvement in physical fitness (based on 6-min walking distance) and that the increase in haemoglobin levels was similar for both groups [ 61 ]. There is also an ongoing randomised controlled study enrolling 76 children with IDA aged 1–17 years (ClinicalTrials.gov Identifier: NCT03523117); patients in this study whose response to the control preparation (oral iron) is unsatisfactory will be treated with FCM in a follow-on study (ClinicalTrials.gov Identifier: NCT04269707).…”
Section: Discussionmentioning
confidence: 99%